Spiritual mindfulness combination with self-regulation on the effect to vital sign and anxiety reduction among pneumonia survivors - Daviq Ayatulloh; Dimas Hadi Prayoga; Diah Priyantini (JKP (Jurnal Keperawatan Padjajaran), 2024)
Background: Pneumonia has become a scary disease since the emergence of the COVID-19 pandemic. The severity of pneumonia often causes sufferers to experience fear and causes the disease to worsen, resulting in the patient's hemodynamics becoming unstable, this condition need an intervention to make the condition better.